Censorship in the PSL Press within the Period of the 1946 Referendum and the Legislative Sejm Election - Swacha, Piotr (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2017)
The main goal of the article is to analyse censorship interventions made in articles raising the topics of the referendum and the election to the Legislative Sejm which were prepared for print in the periodicals of the Polish People’s Party. The material developed by the Main Office of Control of Press, Publications and Shows in Warsaw and by its regional divisions constituted its basic source of information. I conducted a quantitative analysis of the interventions using a sample of the reports of the censorship institution regarding the “Polska Ludowa” periodical. I have also discussed the content removed from print. Within the studied area, censorship most often prevented the PSL periodicals from publishing information regarding the repressions of the PSL’s activists, informing about the organisation of both events and suggesting the fact of forging votes.